Anomalous enhancement of the thermoelectric figure of merit by V co-doping of Nb-SrTiO3 - Ozdogan, K.; Kahaly, M. Upadhyay; Alshareef, H. N.; Schwingenschloegl, U. (AMER INST PHYSICS, 2012)
The effect of V co-doping of Nb-SrTiO3 is studied by full-potential density functional theory. We obtain a stronger increase of the carrier density for V than for Nb dopants. While in Nb-SrTiO3 a high carrier density counteracts a high thermoelectric figure of merit, the trend is inverted by V co-doping. The mechanism leading to this behavior is explained in terms of a local spin-polarization introduced by the V ions. Our results indicate that magnetic co-doping can be a prominent tool for improving the thermoelectric figure of merit. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4714541]
Keywords: NB-DOPED SRTIO3; Physics